The Role of the Signaling Pathways Involved in the Protective Effect of Exogenous Hydrogen Sulfide on Myocardial Ischemia-Reperfusion Injury - Lv, Shuangyu; Li, Xiaotian; Zhao, Shizhen; Liu, Huiyang; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Ischemia/reperfusion (I/R) injury refers to the functional and structural changes in the process of blood flow recovery after ischemia. In addition to ischemia, the blood flow recovery can also lead to very harmful damage, such as obvious cell swelling and irreversible cell necrosis. I/R injury is related with many diseases, including myocardial I/R injury. Myocardial I/R injury refers to the aggravation of ischemic myocardial tissue injury due to sudden disorder of blood circulation. Although there are many studies on myocardial I/R injury, the exact mechanism is not fully understood. Hydrogen sulfide(H2S), like carbon monoxide and nitric oxide, is an important gas signal molecule. It plays an important role in many physiological and pathological processes. Recent studies indicate that H2S can improve myocardial I/R injury, however, its mechanism is not fully understood, especially the involved signal pathways. In this review, we summarize the relevant researches about the role of signaling pathways involved in the protective effects of exogenous H2S on myocardial I/R injury, so as to provide theoretical reference for the future in-depth researches.